2016
DOI: 10.3390/agriculture6010006
|View full text |Cite
|
Sign up to set email alerts
|

Microarray-Based Screening of Differentially Expressed Genes of E. coli O157:H7 Sakai during Preharvest Survival on Butterhead Lettuce

Abstract: Numerous outbreaks of Escherichia coli O157:H7 have been linked to the consumption of leafy vegetables. However, up to the present, little has been known about E. coli O157:H7's adaptive responses to survival on actively growing (and thus responsive) plants. In this study, whole genome transcriptional profiles were generated from E. coli O157:H7 cells (isolate Sakai, stx-) one hour and two days after inoculation on the leaves of growing butterhead lettuce, and compared with an inoculum control. A total of 273 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 67 publications
3
13
0
Order By: Relevance
“…Similarly, transient cold shock in romaine lettuce leaf lysate resulted in upregulation of stx1 but downregulation of eae [50] . However, eae was not differentially regulated during preharvest survival on butterhead lettuce [14] concurring with the results presented by Xicohtencatl-Cortez et al [51] who reported that this gene was not involved in attachment to fresh produce. Again, no direct comparison can take place with the results obtained in the present study due to different quantification strategies.…”
Section: Figure 1 Effect Of Substrate Type and Temperature On The Resupporting
confidence: 90%
See 1 more Smart Citation
“…Similarly, transient cold shock in romaine lettuce leaf lysate resulted in upregulation of stx1 but downregulation of eae [50] . However, eae was not differentially regulated during preharvest survival on butterhead lettuce [14] concurring with the results presented by Xicohtencatl-Cortez et al [51] who reported that this gene was not involved in attachment to fresh produce. Again, no direct comparison can take place with the results obtained in the present study due to different quantification strategies.…”
Section: Figure 1 Effect Of Substrate Type and Temperature On The Resupporting
confidence: 90%
“…Mahmoudzadeh et al [13] studied the transcription of stx1A and stx2A during growth on ground beef stored at 4 o C for up to 7 days. Finally, Van der Linden et al [14] used a microarray-based screening to assess the transcriptomic response during preharvest survival on butterhead lettuce.…”
Section: Introductionmentioning
confidence: 99%
“…Plant cell recognition of Microbe-Associated Molecular Patterns (MAMPs) of human bacterial pathogens can trigger the production of Pattern-Triggered Immunity (PTI)-associated defense responses (Garcia et al, 2014), including a decrease in stomatal aperture width (Melotto et al, 2006;Roy et al, 2013). On the other hand, bacteria might counter-attack the plant responses by subverting the stomatal closure defense (Roy et al, 2013) or activating genes associated with oxidative stress tolerance and antimicrobial resistance (Van der Linden et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Spinach was selected as it is relevant to large-scale STEC outbreaks [18], and we have previously shown specific adherence to spinach roots [14, 15, 6]. High-throughput screening enables wholesale analysis and previous global transcriptomic analysis has shown induction of STEC fimbrial and afimbrial adhesins in lettuce leaf lysates [19–21]. In a similar manner, high-throughput negative- and positive-selection approaches have identified colonisation factors, e.g.…”
Section: Introductionmentioning
confidence: 99%